2019
DOI: 10.3390/su11072016
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Orientation and Tilt Angle for Maximizing in-Plane Solar Irradiation for PV Applications in Japan

Abstract: To maximize the direct insolation received by flat-plate photovoltaic (PV) modules, the tilt angle is usually the site’s latitude and the modules are oriented towards the equator. However, this may not be the optimal placement, as the local climatic conditions will influence the optimal orientation and tilt angle. Transposition models can be used to simulate the insolation on planes with various tilts and azimuths, using a single set of (horizontal) global and diffuse irradiance measurements. Following this me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Although operators cannot control the water demands in urban WPN as they do in irrigation systems, this did not avoid the use of photovoltaic technology to supply pumping devices in many regions of the world such as the USA [27,28], India [29], Finland [30], Brazil [31], Malaysia [32], and Spain [33]. In areas with high potential (semi-arid regions and high irradiation levels), many practitioners implement this technology for sizing PV systems [34][35][36][37], minimizing the number of PV modules [38], optimizing the tilt angle [39,40], and comparing the environmental and economic impacts of supplying pumps with electricity grids or PV cells [41]. Photovoltaic systems may influence the voltage quality in electricity grids [42], affecting the voltage profile and harmonic distortion of the current and voltage, although some customer-side energy storage systems can make voltage management more economical [43], we proposed using the energy produced in pumping devices that may work as a standalone system.…”
Section: Introductionmentioning
confidence: 99%
“…Although operators cannot control the water demands in urban WPN as they do in irrigation systems, this did not avoid the use of photovoltaic technology to supply pumping devices in many regions of the world such as the USA [27,28], India [29], Finland [30], Brazil [31], Malaysia [32], and Spain [33]. In areas with high potential (semi-arid regions and high irradiation levels), many practitioners implement this technology for sizing PV systems [34][35][36][37], minimizing the number of PV modules [38], optimizing the tilt angle [39,40], and comparing the environmental and economic impacts of supplying pumps with electricity grids or PV cells [41]. Photovoltaic systems may influence the voltage quality in electricity grids [42], affecting the voltage profile and harmonic distortion of the current and voltage, although some customer-side energy storage systems can make voltage management more economical [43], we proposed using the energy produced in pumping devices that may work as a standalone system.…”
Section: Introductionmentioning
confidence: 99%
“…In the water industry, many works have been performed in pressurized water networks [19,[29][30][31] and in pressurized irrigation networks [32][33][34] where the energy consumption profiles influence the PV installation [35][36][37]. Many approaches have focused on energy production optimizing the tilt angle [38][39][40][41], by analyzing the shadows' influence on this energy production [42][43][44], or obtaining the influence of cleaning in energy production [45], while others have focused on the viability of energy storage in batteries [20,44,46,47] or the maximization of the battery charge [48] or the influence of electric cost in the batteries' dimension and feasibility [49]. Battery storage methods have been shown to be the most effective choice for the cost study presented with the lowest payback periods, but we should also consider their management and replacement [48,50].…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that adjusting tilt angles six times per year harvests 99.5% of the solar radiation that could be achieved with daily PV panel adjustment [43]. Yu et al [13] established a database to optimize the PV applications in Japan. The authors focused on the orientations and inclinations of installing PV modules as two major factors to achieve the aim of their study, while Han and Kim [44] developed an optimization-based framework to design renewable energy systems for the residential sector in Korea.…”
Section: Related Literaturementioning
confidence: 99%
“…Although several aspects regarding the performance and design of PV modules have been examined in the literature, a systematic procedure for the assessment of critical performance and design parameters for installation of PV modules that can be easily accessed by practitioners is required, particularly, the orientation and inclination parameters [13]. In an attempt to address this, factorial design analysis, along with a visualization aid, for designing solar energy systems for buildings are adopted in order to assess and choose the best installation of PV modules at various inclinations and orientations on roofs and elevations of buildings.…”
Section: Introductionmentioning
confidence: 99%